Innovation networks and clusters: the case of Chengdu Furniture Enterprise - Liqiong, Sun (2014)
In recent years, research within national and international studies, highlights the lack of studies exploring the relationship between the network structure and the innovation cluster network in a micro -level perspective. This thesis fills the gap by studying the influence on the cluster innovation process of the entire and individual features of the structure of the cluster innovation network. This thesis uses a case applied to the furniture innovation network in Chengdu with the aid of methods of social network analysis and statistical software for social sciences - UCINET. This study includes as main contents: (1) the study of the influence of the characteristics of the innovation network cluster as dens ity and centrality in the process of innovation cluster, and (2) through the empirical study, the analysis of the influence of individual characteristics of the structure as a mediator of the innovative performance of companies. This thesis presents the following conclusions: firstly, the analysis of the advantages of the innovation cluster network and the influence on innovation cluster through the structure characteristics of the enterprise network, taking as an example the companies with high centrality , as they occupy a privileged position in the network and can more easily obtain the scarce innovation resources; secondly the analysis of the innovative performance, noting that through the individual characteristics of the structure, structural gaps of t he firms have a positive influence on their innovative performance; Thirdly, this paper was applied to the case of the network of Chengdu Furniture innovation cluster. Networks are constantly changing. Through the development and improvement of networks on Chengdu Furniture clusters, the innovation potential of clusters and the innovation of enterprises can be improved.